O novo papel da vítima no processo penal: uma releitura dos poderes do assistente de acusação - Rocha, Cristiano Medina da (2024)
The emergence of Victimology has given rise to a series of questions about the role of the victim in the context of criminal investigations and criminal proceedings. Having overcome the embryonic phases on the subject, the rediscovery of this figure in contemporary times has guided national legislation and international documents conveying human rights to increasingly place her at the level of a subject of rights, especially regarding to the protection of their dignity through the pursuit of truth and justice. Hence why Brazilian criminal procedural law must be interpreted in accordance with the constitutional guidelines regarding the position in which the victim should be allocated, overcoming understandings that were previously considered to be pacified. In this context, the offended party must come to be seen as an adjunct to the Public Prosecutor's Office, authorized, therefore, to enable prosecution assistance in criminal actions, with a view to participating extensively in all acts applicable to criminal prosecution, including being able to request the production of evidence, interview witnesses, participate in oral debates, present written arguments and file all appeals whose ministerial legitimacy is already accepted. In this context, it is proposed to re-read the legal provisions that govern the matter, with a view to conforming them to the current constitutional order